Models and perspectives on the adoption of disruptive digital technologies in small rural enterprises - Garita-Rodríguez, César Orlando (2026)
The adoption of novel technologies by small rural enterprises is a necessary process to achieve greater competitiveness in today’s aggressive markets. These companies need to increase their digital maturity level in the short term through the adoption of disruptive technologies such as artificial intelligence, mobile applications, social networks, data analysis, the internet of things, and cloud services. This article explores different models and perspectives on the adoption of disruptive digital technologies in small rural enterprises worldwide. The article presents a scientific systematic literature review carried out based on specific research questions, which served as a base to perform a bibliographic search on the SCOPUS database. The resulting articles were selected and organized into specific categories to facilitate their analysis. Consequently, the most important findings of the review are summarized in regards to: the main challenges that companies face regarding the adoption of new technologies; the most used methodologies to assess digital maturity; the metrics designed to measure the impact of the adoption of new technologies; the most commonly applied innovative technologies to promote digital transformation; and relevant case studies regarding the successful adoption of innovative technologies. The presented work aims to assist small rural enterprises facing the challenge of digital transformation in developing countries.